Development and Evaluation of the Rapid and Sensitive RPA Assays for Specific Detection of Salmonella spp. in Food Samples - Zhao, Liwei; Wang, Jianchang; Sun, Xiao Xia; Wang, Jinfeng; Chen, Zhimin; Xu, Xiangdong; Dong, Mengyuan; Guo, Ya-nan; Wang, Yuanyuan; Chen, Pingping; Gao, Weijuan; Geng, Yunyun (Frontiers in Cellular and Infection Microbiology, 2021)
Salmonella has been considered as a main food-borne pathogen leading to serious foodborne diseases. In the current study, in order to detect Salmonella targeting the conserved sequence of invasion protein A (invA), an isothermal real-time recombinase polymerase ampliﬁcation (RPA) and lateral flow strip detection (LFS RPA) were implemented. The Real-time RPA was performed in a portable florescence scanner at 39 °C for 20 min, while the LFS RPA was performed in an incubator block at 39 °C for 15 min, under the same condition that the amplifications could be inspected by the naked eyes on the LFS within 5 min. With the help of LFS RPA assay, the detection limit of Salmonella DNA was 1.1× 102 fg, which was 10 times lower than that of the real-time RPA and real-time PCR assays. Moreover, the practicality of the way to discover Salmonella was validated with artificially contaminated lamp, chicken and broccoli samples. On the basis of the real-time and LFS RPA assays, the analyzing time dropped from 60 min to proximately 5-12 min as the results were equally reliable when comparing with the real-time PCR assay. Finally, no cross-reactivity with other pathogens appeared in both of the assays and good stability are presented as well. All of these helps to manifest that the developed RPA assays were simple, rapid, sensitive, and credible, and they could be a potential point-of-care test required mere resources.